Trade-Off Exploration and Exploitation as Moderators: How does Technological Heterogeneity among Cooperators Affect Firms Financial Performance? - Li, Liu (Asian Economic and Financial Review, 2020)
Drawing on a resource-based view, this study focused on the relationship between technological heterogeneity among cooperators and the firm’s financial performance. An important influence mechanism was that technological heterogeneity among cooperators makes the firm’s knowledge recombination more diversified so that the firm can create more products to capture market demands and make a profit. In particular, the intra-firm learning strategies, namely exploratory learning, exploitative learning or ambidexterity, have a strong influence on the absorption of external heterogeneous knowledge. Thus, technological heterogeneity among cooperators and the intra-firm learning strategies may have an interactive impact on the firm’s financial performance. Based on the patent data and financial data of 31 Chinese innovative firms from 2000 to 2016, we found that technological heterogeneity among cooperators positively affected the firm’s financial performance. The firm’s exploitative learning negatively moderated the relationship between technological heterogeneity among cooperators and the firm’s financial performance. The firm’s ambidexterity positively moderated the relationship between technological heterogeneity among cooperators and the firm’s financial performance. Finally, the suggestions about organizational learning and sustainable profitability are discussed.